2024
DOI: 10.1037/cou0000733
|View full text |Cite
|
Sign up to set email alerts
|

Perceived control moderates the internalized stigma model of seeking mental health services in distressed older adults.

Dallas J. Murphy,
Corey S. Mackenzie,
Robert P. Dryden
et al.

Abstract: Older adults are especially unlikely to seek mental health services, and internalized stigma is a key reason why. However, little research has investigated which older adults are particularly likely to have stigma influence help-seeking. To address this, we tested whether perceived control (PC) moderates an internalized stigma model in which public stigma is internalized as self-stigma, which negatively predicts help-seeking attitudes and help-seeking intentions. We employed moderated mediation analysis of cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…First, this work can be extended to clinical samples to understand the influence of personality on the help seeking of more at-risk populations. Second, research has found other established predictors, such as experiential avoidance (Brenner et al, 2020; Murphy & Mackenzie, 2023), perceived control (Murphy et al, 2024), and mental health literacy (Mackenzie et al, 2023) to moderate the internalized stigma model, and research might explore personality as a moderator. Third, research has explored longitudinal changes in personality (e.g., Roberts et al, 2006; Srivastava et al, 2003); similar work that includes mental health service use variables would help clarify the interactions among these variables over time.…”
Section: Discussionmentioning
confidence: 99%
“…First, this work can be extended to clinical samples to understand the influence of personality on the help seeking of more at-risk populations. Second, research has found other established predictors, such as experiential avoidance (Brenner et al, 2020; Murphy & Mackenzie, 2023), perceived control (Murphy et al, 2024), and mental health literacy (Mackenzie et al, 2023) to moderate the internalized stigma model, and research might explore personality as a moderator. Third, research has explored longitudinal changes in personality (e.g., Roberts et al, 2006; Srivastava et al, 2003); similar work that includes mental health service use variables would help clarify the interactions among these variables over time.…”
Section: Discussionmentioning
confidence: 99%